EFFORTS TO IMPROVE STUDENTS' LEARNING MOTIVATION - Mohammad Imam Sufiyanto; Khairunisa; Roviandri; Hesti Kusumawati; Rocyhan Yasin (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
This study aims to examine the learning motivation of elementary school students, identify the efforts made by teachers to enhance students’ motivation, and analyze the supporting and inhibiting factors involved. The study employs a qualitative approach using a descriptive method. The researcher collected data through interviews, observations, and documentation involving five teachers at MI Nurul Islam, Pamekasan. The findings reveal that students’ learning motivation varies, ranging from high to low levels, influenced by both internal and external factors. Teachers make several efforts to improve students’ motivation, including creating an enjoyable learning environment, applying innovative teaching methods such as discussions, quizzes, and audio-visual media, providing rewards, and involving parents in the educational process. Supporting factors include parental support, a conducive learning environment, and the use of engaging learning media. In contrast, inhibiting factors consist of limited facilities, students’ low basic abilities, and a lack of support from the family environment. Therefore, creative and collaborative teachers play a crucial role in enhancing students’ learning motivation.